1995
DOI: 10.1080/02652039509374276
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of wort containing added ochratoxin A and fumonisins B1and B2

Abstract: Ochratoxin A (OA), fumonisin B1 (FB1) and fumonisin B2 (FB2) were added to wort at levels of 0.19, 0.95 and 0.95 micrograms/ml, respectively, and fermented for up to 8 days by three strains of Saccharomyces cerevisiae. Decreases of OA in the beer over this period were estimated from straight line slopes to be 2-13%. Losses of FB1 and FB2 were estimated to be 3-28% and 9-17% respectively. Some OA was taken up by the yeast, up to 21% in a detailed study with one strain. In contrast, uptake of fumonisins by yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 17 publications
0
47
1
3
Order By: Relevance
“…Recent investigations demonstrate that Saccharomyces cerevisiae strains are able to remove OTA from plant raw material during fermentation of wine, beer, or sourdough [23,[26][27][28][29]. Some authors reported decreasing ochratoxin levels during winemaking [26,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations demonstrate that Saccharomyces cerevisiae strains are able to remove OTA from plant raw material during fermentation of wine, beer, or sourdough [23,[26][27][28][29]. Some authors reported decreasing ochratoxin levels during winemaking [26,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Corn starch and corn syrup are among the adjuncts alternatively used for beer production, but no contamination by fumonisins has been found in these materials 4,28 . FB 1 is stable to heat 1,19,20 and to conditions found during fermentation of corn to produce ethanol 37 .…”
Section: Introductionmentioning
confidence: 99%
“…OTA residues may occur in beer, if the toxin is present in barley and malt used in its making 2 . The fermentation of wort to which OTA had previously been added showed that the toxin decreased from 2 to 13% 37 . A remainder of 13 to 32% of the toxin was found in the final product when OTA contaminated malt was obtained from barley inoculated with Penicillium verrucosum and subsequently used for beer making 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the aforementioned were tested in vivo; however, their activity was not as high as expected except for activated charcoal 54,106 . In this case, use has been rejected due to essential nutrient retention and animal poisonings 7,45,54 .…”
Section: Detoxification Of Ochratoxin Amentioning
confidence: 99%